Evaluation of patient acceptance and compliance with clear aligners vs. lingual braces: A randomized trial - Ahmed A Alfawzan (Wolters Kluwer Medknow Publications, 2024)
Background: The efficacy of orthodontic treatments is often influenced by patient acceptance and compliance. This study aims to compare patient acceptance and compliance between clear aligners and lingual braces in a randomized clinical trial. Materials and Methods: A total of 100 patients requiring orthodontic treatment were randomly allocated into two groups: clear aligners (n = 50) and lingual braces (n = 50). Data on patient acceptance and compliance were collected through self-reported questionnaires and clinical observations over a period of 12 months. Results: Patient acceptance was significantly higher in the clear aligner group, with 80% reporting high levels of comfort, compared to 60% in the lingual braces group (P < 0.05). Compliance rates were 92% for clear aligners and 85% for lingual braces (P = 0.1). Conclusion: Clear aligners showed a higher level of patient acceptance and a slightly better compliance rate, although the difference was not statistically significant. These findings suggest that clear aligners may be a preferable option for patients prioritizing comfort.